Influence of five years of antenatal screening on the paediatric cystic fibrosis population in one region. Issue 4 (1st April 1998) - Cunningham, Steven; Marshall, Tom
Abstract : BACKGROUND: Antenatal screening for cystic fibrosis has been endorsed by the US National Institutes of Health. Edinburgh is the only city in the UK with an established routine antenatal screening programme for cystic fibrosis. AIMS: To report the change in numbers of infants diagnosed with cystic fibrosis born in Edinburgh after the introduction of antenatal screening for the disease. POPULATION: Infants diagnosed as having cystic fibrosis (by sweat test or genotyping, or both) in the seven years before antenatal testing (1984–90) and the first five years of antenatal testing (1991–95). Children born in this region who had moved before diagnosis were identified from the UK cystic fibrosis survey database. RESULTS: The incidence of cystic fibrosis decreased from an average of 4.6 to 1.6 children each year with antenatal screening. The reduction in the incidence (65%) was greater than that accounted for by prenatal diagnosis and termination (36%). Of the eight children born with cystic fibrosis during the period of antenatal screening, five had been subject to antenatal screening: three had only one mutation identified, one was missed due to a laboratory error, and one was identified as a one in four risk, but prenatal diagnosis was not performed. CONCLUSIONS: Antenatal testing for cystic fibrosis has successfully reduced the incidence of cystic fibrosis in this region. Although the numbers are small, it is possible that the reduction in numbers may have been greater than might be expected from antenatal screening alone.